2019
DOI: 10.1101/774349
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diversity in CRISPR-based immunity protects susceptible genotypes by restricting phage spread and evolution

Abstract: AbstractDiversity in host resistance often associates with reduced pathogen spread. This may result from ecological and evolutionary processes, likely with feedback between them. Theory and experiments on bacteria-phage interactions have shown that genetic diversity of the bacterial adaptive immune system can limit phage evolution to overcome resistance. Using the CRISPR-Cas bacterial immune system and lytic phage, we engineered a host-pathogen system where each bacterial host … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 72 publications
2
15
1
Order By: Relevance
“…The drop in local adaptation with time is consistent with the overall drop in phage density we observed in most phage populations (Figure 2b). This suggests that the phages are losing the coevolutionary arms race with their hosts which is in line with previous studies showing that CRISPR immunity often yields phage extinction in this system [29][30][31]. Besides, we found some evidence that evolution of new immunities may also be due to the second active CRISPR-Cas system (CR3) in this host in which we detected spacer acquisition starting at day 3 or 4 (Table S4).…”
Section: Phage Coevolution Across Space and Timesupporting
confidence: 91%
“…The drop in local adaptation with time is consistent with the overall drop in phage density we observed in most phage populations (Figure 2b). This suggests that the phages are losing the coevolutionary arms race with their hosts which is in line with previous studies showing that CRISPR immunity often yields phage extinction in this system [29][30][31]. Besides, we found some evidence that evolution of new immunities may also be due to the second active CRISPR-Cas system (CR3) in this host in which we detected spacer acquisition starting at day 3 or 4 (Table S4).…”
Section: Phage Coevolution Across Space and Timesupporting
confidence: 91%
“…The evolution of increased host range is predicted to peak at intermediate levels of host diversity: low diversity results in weak selection for increased host range, because parasites may frequently encounter the same host genotype, whereas high diversity slows the response to selection by limiting the effective population size of the parasite (Benmayor et al 2009;Chabas et al 2018). Consistent with this prediction, Common et al (2020) found that generalist phages evolved readily in bacterial populations with intermediate diversity, but less so when host diversity was low and not at all when it was maximal. Sant et al (2021) similarly found that generalist phages evolved in moderately diverse bacterial populations, where the low probability of repeatedly encountering the same host genotype selected against specialists.…”
Section: How Do Parasites Evolve In Genetically Diverse Host Populati...mentioning
confidence: 89%
“… 2005 ; Lively 2010 ), and the protective effect of host variation has been empirically demonstrated in a number of experimental (e.g., Altermatt and Ebert 2008 ; Common et al. 2020 ) and natural systems (Ekroth et al. 2019 ), especially those in which rapid host evolution is unlikely (Gibson and Nguyen 2020 ).…”
Section: Discussionmentioning
confidence: 99%